Exit path : how to win the startup end game - Parang, Touraj (McGraw Hill-Ascent Audio, 2022)
In 2008, Touraj Parang's award-winning startup, Jaxtr, had 10 million users, raised nearly $20 million from top-tier Silicon Valley investors, and seemed poised to sail straight through the Great Recession. But, by January of 2009, Jaxtr's only hope for survival was to find a buyer-sadly, it was too late for that. In Exit Path, Touraj draws on the lessons learned from that chaotic experience and the extraordinary successes that followed once he made creating and executing an exit strategy a top priority. In this comprehensive guide, you'll learn that implementing an exit strategy early will empower you to take charge of your startup's ultimate fate, maximizing its potential for success while mitigating the risks of failure. Exit Path walks you through actionable steps to devise and execute an effective exit strategy, starting with a fresh new perspective on the critical importance of creating a viable sale option for your startup. You'll learn why creating your exit strategy is necessary well before you're contemplating an exit, regardless of the stage of your startup. You'll also discover how to create your own exit plan, how to make your plan a reality through personal and business relationships, and how to approach and negotiate with acquirers for an outcome best aligned with your values and ambitions should the need arise.